The incidence of other gastroenterological disease following diagnosis of irritable bowel syndrome in the UK: a cohort study - Canavan, Caroline; Card, Timothy R.; West, Joe (Public Library of Science, 2014)
BACKGROUND: Guidelines recommend Irritable Bowel Syndrome (IBS) diagnosis and management in primary care with minimal investigations; however little evidence exists regarding risk of organic gastrointestinal conditions following diagnosis of IBS and how such risks vary over the long term. This study assesses excess incidence of coeliac disease, inflammatory bowel disease (IBD) and colorectal cancer (CRC) and variation with age and time after IBS diagnosis.